OPTIMALISASI SARANA DAN PRASARANA SEPAK BOLA SEBAGAI PENUNJANG PEMBINAAN ATLET MUDA BERPRESTASI - Andi Sri Rafiqa Hayu; Andi Muhammad Fatir; Ade Ananda; Nabila; Andi Zulqadri; Suci Rahmadani; Dandi Ibrahim; Nurlindah; Fadil; Rifaldi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Developing young athletes is a crucial factor in improving sports performance, particularly in soccer. The success of the development process is determined not only by the quality of the coach and training program, but also by the availability and management of adequate facilities and infrastructure. Standard facilities and infrastructure can support effective training, improve technical skill mastery, and create a safe and comfortable training environment for young athletes. This article aims to examine the importance of optimizing soccer facilities and infrastructure to support the development of high-achieving young athletes. The method used is a literature review, reviewing various scientific sources, including journals, books, and documents relevant to the research topic. The results of the study indicate that optimizing soccer facilities and infrastructure plays a crucial role in improving the quality of the training process, supporting the development of athletes' technical, physical, tactical, and mental abilities, and minimizing the risk of injury. Furthermore, proper facility management and maintenance can increase training motivation and support the ongoing success of athlete development programs. Therefore, optimizing soccer facilities and infrastructure is a crucial aspect that needs to be considered in developing young athletes capable of achieving success at the regional, national, and international levels.